From textbooks to online sources: An Investigation of drug information resource preference and utilization among healthcare Professionals - Abdulkader Hayek; Sathvik B. Sridhar; Syed Arman Rabbani; Javed Shareef (Elsevier, 2024)
Background: Providing drug information (DI) is one of the essential pharmaceutical care services. Previous research has documented varying DI preferences and utilization practices among Healthcare Professionals (HCPs). This study aimed to determine the preference and utilization of DI resources among HCPs and identify the main barriers that impede their ability to utilize them. Methods: A cross-sectional survey was conducted in selected government, private hospitals, and primary healthcare clinics. A thirteen-item survey instrument was developed to assess the utilization, accessibility, preferences, and satisfaction with various DI resources and barriers. HCPs meeting the inclusion criteria were identified and contacted. The collected data were analyzed using the Statistical Package for Social Sciences (SPSS) 27. Results: 311 responses were considered for the final analysis. Most HCPs who contributed to this survey were pharmacists, nurses, and physicians. Google was the most frequently used reference resource, at 64.3% (n = 200), followed by other subscription-based databases at 36% (n = 112) and package inserts at 30.5% (n = 95). UpToDate was the most commonly used database, i.e., 42.1% (n = 131) (RII = 0.749196). Treatment was the most common category of DI, and 69.8% (n = 217) searched (RII = 0.899517). Lack of time, 46% (n = 201), was the most limiting factor for seeking DI. Variables such as work experience, practice setting, education level, and continuing medical education hours were the significant (p < 0.05) predictors of some DI utilization components and preferences. Conclusion: This study shows differences in preference and utilization of drug information resources (DIR) by HCPs, depending upon their clinical practice and background. Therefore, educational strategies are needed to empower HCPs about DIR.